1993
DOI: 10.1111/j.1365-2559.1993.tb00090.x
|View full text |Cite
|
Sign up to set email alerts
|

A histochemical and immunohistochemical study of extra‐ocular sebaceous carcinoma

Abstract: A histochemical and immunohistochemical study of five cases of extra-ocular sebaceous carcinoma was performed using formalin-fixed and paraffin-embedded tissue specimens. Histochemically, the clear cells of sebaceous carcinomas were negative with periodic acid-Schiff and alcian blue staining. Immunohistochemically, the tumour cells of sebaceous carcinomas showed positive reactions for epithelial membrane antigen, human milk fat globules subclass 1, human milk fat globules subclass 2 and Leu M1, but did not exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 17 publications
3
59
0
Order By: Relevance
“…Strong reactivity to epithelial membrane antigen and human milk fat globules subclasses 1 and 2 has been demonstrated. 8 A sebaceous carcinoma of salivary gland origin was also considered in the differential diagnosis. Intrasalivary sebaceous carcinoma is an extremely rare, low-grade malignancy most often occurring in the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
“…Strong reactivity to epithelial membrane antigen and human milk fat globules subclasses 1 and 2 has been demonstrated. 8 A sebaceous carcinoma of salivary gland origin was also considered in the differential diagnosis. Intrasalivary sebaceous carcinoma is an extremely rare, low-grade malignancy most often occurring in the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that epithelial membrane antigen, cytokeratin 7, CAM 5.2, and androgen receptors can be used to suggest sebaceous differentiation in specific diagnostic contexts with variable success. [12][13][14][15][16][17][18][19][20] A recent study investigated the use of antibodies directed against proteins associated with lipid droplets, known as the PAT or perilipin family including a monoclonal antibody to adipophilin and polyclonal antibodies to perilipin and TIP47/ PP17. 17 Adipophilin is reported to be expressed in cells of lactating mammary epithelium, adrenal cortex, male reproductive system (Sertoli and Leydig cells), steatotic hepatocytes in alcoholic cirrhosis, and liposarcomas.…”
mentioning
confidence: 99%
“…[28][29][30][31][32][33][34][35][36][37][38][39][40] Although ocular sebaceous carcinoma is said to have a predilection for Asians, this has not been our experience; this may reflect selection bias based upon our practice profiles, however. Patients classically develop painless nodules or papules along the eyelid margin or in palpebral conjunctiva.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In practice, ocular sebaceous carcinoma is far more common than its extraocular counterpart, although both are aggressive and potentially lethal malignant neoplasms. [3][4][5][28][29][30][31][32][33][34][35][36][37][38][39] Figure 2 Sebaceoma. Sebaceoma is characterized by a diffuse admixture of germinative epithelia and sebocytes with no compartmentalized, organized pattern as seen in sebaceous hyperplasia and sebaceous adenoma (a).…”
Section: Introductionmentioning
confidence: 99%